Analysis of Planetary Gear Fatigue Strength of Wind Turbine Under Weibull Distribution Random Load - Mingming Su; Mutellip Ahmat; Guangyao Sun (Jixie chuandong)
In order to quickly and accurately evaluate the fatigue life of the planetary gear system of wind turbine， according to the distribution relationship between the input torque of the planetary gear system and the wind speed， the two-parameter weibull random load spectrum corresponding to different wind speed is compiled， and the load spectrum is statistically processed by rain flow counting method. The finite element analysis of planetary gear train in ANSYS is carried out to obtain its structural stress response. Based on Minner's linear cumulative damage theory and nCodeDesignLife， fatigue life is estimated. The fatigue life of the planetary gear train corresponding to the starting wind speed， the rated wind speed and the average annual wind speed of the wind turbine is emphatically analyzed， and the fatigue damage of each gear is obtained， which provided a theoretical basis for the design of the planetary gear train fatigue strength of the wind turbine.